Multi-Agent Simulation and Management Practices - Siebers, Peer-Olaf; Aickelin, Uwe; Celia, Helen; Clegg, Christopher (IDEAS Group, 2007)
Intelligent agents offer a new and exciting way of understanding the world of work. Agent-Based Simulation (ABS), one way of using intelligent agents, carries great potential for progressing our understanding of management practices and how they link to retail performance. We have developed simulation models based on research by a multi-disciplinary team of economists, work psychologists and computer scientists. We will discuss our experiences of implementing these concepts working with a well-known retail department store.